The colonization and cultural identity crisis in chinua achebe's no longer at ease - Sri Haryati (The English Department, Faculty of Languages and Arts, Universitas Negeri Surabaya, 2021)
Abstract This study analyzes the colonization and cultural identity crisis in Chinua Achebe’s No Longer at Ease. This novel as the second novel by Chinua achebe is a sequel novel has a post-colonial background as a main theme. Obi as the main character in this novel get scholarship to study abroad, struggle after nigeria get its independence and get difficulties looking for his identity between two culture, the origin and western culture. This analysez aim to potrayed the colonization in the novel and to find the cause why the nigerian lost their identity because of the colonization. To get the probability data, this study is using the post-colonial approach and theory, and identity crisis theories. To analyze, this study uses a critical interpretation of data analysis. In conclusion, Obi’s identity is lost because of the colonization and he get influence from british culture. This study support Foucault’s persepective of multicultural society. Keywords : colonization, culture identity crisis